1997
DOI: 10.5014/ajot.51.2.91
|View full text |Cite
|
Sign up to set email alerts
|

Tactile Defensiveness and Stereotyped Behaviors

Abstract: The results suggest that clinicians should include observations of stereotyped behaviors, particularly behavioral rigidities, in conjunction with assessments of sensory defensiveness because these are related phenomena that may pose unique challenges for children with developmental disabilities and autism. Further study is needed to determine the causal mechanisms responsible for these relationships.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
113
1
11

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 198 publications
(128 citation statements)
references
References 7 publications
(11 reference statements)
3
113
1
11
Order By: Relevance
“…Alterations of synaptic modulation in autism, possibly related to the polymorphism of the serotonin transporter, has been suggested to affect thalamo-cortical connectivity and consequently leading to the development of sensory abnormalities (Chugani, 2002). Finally, the most compelling evidence linking the serotoninergic system and the thalamus to sensory abnormalities in autism comes from the involvement of serotonin in obsessive compulsive behaviors (Gilbert et al, 2000) and the recently reported association between these symptoms and sensory abnormalities in autism (Baranek et al, 1997). However, in spite of this mounting evidence, it remains unclear if the nature of this relationship is associative or causative.…”
Section: Discussionmentioning
confidence: 99%
“…Alterations of synaptic modulation in autism, possibly related to the polymorphism of the serotonin transporter, has been suggested to affect thalamo-cortical connectivity and consequently leading to the development of sensory abnormalities (Chugani, 2002). Finally, the most compelling evidence linking the serotoninergic system and the thalamus to sensory abnormalities in autism comes from the involvement of serotonin in obsessive compulsive behaviors (Gilbert et al, 2000) and the recently reported association between these symptoms and sensory abnormalities in autism (Baranek et al, 1997). However, in spite of this mounting evidence, it remains unclear if the nature of this relationship is associative or causative.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, evidence suggests that sensory problems in autism are more common during childhood than during adulthood (Baranek, Foster, & Berkson, 1997). Kern et al (2006) reported that sensory problems in autism tend to be ameliorated with age.…”
Section: Scientific Researchmentioning
confidence: 99%
“…NIH-PA Author Manuscript NIH-PA Author Manuscript estimated to occur in 5% of the general population (Ahn, Miller, Milberger, & McIntosh, 2004) and seem to pose a unique challenge for people with developmental disabilities (Baranek, 2002), including autism, attention deficit hyperactivity disorder (ADHD), fragile X syndrome, and other developmental disabilities (Ayres & Tickle, 1980;Baranek, 1999;Baranek & Berkson, 1994;Baranek, Foster, & Berkson, 1997;Cermak & Daunhauer, 1997;Grandin, 1992;Kinnealey, 1973;Larson, 1982;Mangeot et al, 2001;Miller et al, 1999). Understanding the neurobiological processes associated with sensory processing disruptions is important to developing appropriate preventative and intervention approaches.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%